Pengaruh Growth Option dan Green Intellectual Capital Terhadap Sustainability Performance - Tambunan, Rupianna (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the influence of Growth Option and Green Intellectual Capital on Sustainability Performance in companies listed in the SRI-KEHATI Index on the Indonesia Stock Exchange. The approach used is quantitative with panel data regression analysis method, and data processing is done using Eviews-12 software. The research sample consists of 25 companies selected through a purposive sampling method with the criteria of companies that are consistently listed in the SRI-KEHATI Index during the observation period. The data used are secondary data obtained from the annual report and sustainability report of each company. The results of the study indicate that Growth Option has no effect on Sustainability Performance, which means that the company's growth opportunities have not been followed by an increase in commitment to sustainability aspects. In contrast, Green Intellectual Capital has a positive and significant effect on Sustainability Performance, which indicates that environmentally oriented management of knowledge, skills, and innovation can improve the company's sustainability performance.